2019
DOI: 10.3389/fnins.2019.01082
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Sex on Consequences of Childhood Maltreatment: From Clinical Studies to Animal Models

Abstract: Stress has pronounced effects on the brain, and thus behavioral outputs. This is particularly true when the stress occurs during vulnerable points in development. A review of the clinical literature regarding the moderating effects of sex on psychopathology in individuals exposed to childhood maltreatment (CM) is complicated by a host of variables that are difficult to quantify and control in clinical settings. As a result, the precise role of sex in moderating the consequences of CM remains elusive. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 149 publications
(301 reference statements)
2
87
0
Order By: Relevance
“…Some of the most compelling evidence comes from imaging showing that exposure to CM causes more pronounced reduction in the size of the hippocampus and the corpus callosum in males compared with females. Sex differences in prefrontal cortex activation and connectivity were also reported in the few fMRI studies that had sufficient power to examine CM‐by‐sex interaction (White & Kaffman, ). In addition, a systematic review conducted by Gershon et al () found that more than half of the 19 studies conducted in adolescents reported significant sex‐by‐CM interaction that was notable for worse clinical outcomes in males exposed to CM.…”
Section: The Role Of Sex In CM Outcomes and The Problematic Unisex Asmentioning
confidence: 76%
See 4 more Smart Citations
“…Some of the most compelling evidence comes from imaging showing that exposure to CM causes more pronounced reduction in the size of the hippocampus and the corpus callosum in males compared with females. Sex differences in prefrontal cortex activation and connectivity were also reported in the few fMRI studies that had sufficient power to examine CM‐by‐sex interaction (White & Kaffman, ). In addition, a systematic review conducted by Gershon et al () found that more than half of the 19 studies conducted in adolescents reported significant sex‐by‐CM interaction that was notable for worse clinical outcomes in males exposed to CM.…”
Section: The Role Of Sex In CM Outcomes and The Problematic Unisex Asmentioning
confidence: 76%
“…In addition, a systematic review conducted by Gershon et al () found that more than half of the 19 studies conducted in adolescents reported significant sex‐by‐CM interaction that was notable for worse clinical outcomes in males exposed to CM. Interestingly, no consistent sex‐by‐CM interaction was found in the 14 studies examining this issue in adulthood (Gershon et al, ), a finding that was replicated in three additional large meta‐analyses (White & Kaffman, ).…”
Section: The Role Of Sex In CM Outcomes and The Problematic Unisex Asmentioning
confidence: 97%
See 3 more Smart Citations